PENDEKATAN PROJECT BASE LEARNING DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SEKOLAH MENENGAH KEJURUAN (SMK) - kartiwa, yudi (PT. Solusi Komunikasi Terapan, 2023)
In this scientific work, the author do research to describe the approach of project base learning in improving the quality of learning in SMK. The method used is descriptive with qualitative approach. Data collection was done by interview, observation and documentation study. The result of the research shows that with the approach of project base learning can realize the quality of learning, this is reflected from the planning, implementation and assessment conducted by the teacher is good enough and in accordance with the applicable provisions. Through this approach during the learning process of student learning motivation is very high, they have good initiative and creativity during the learning, cooperation and ability of students in finding solutions to problems can be built properly.